Maternal mortality: causes and prevention strategies (Research, Society and Development, 2020)
Integrative Literature review study, carried out in the Virtual Health Library and in the databases: Latin American and Caribbean Literature in Health Sciences and Medical Literature Analysis and Retrieval System Online. Aiming to analyze in the national and international literature the scientific evidence about the causes of maternal deaths and the strategies used for its prevention. After analyzing the inclusion and exclusion criteria, a universe of ten studies was obtained. Showing that the main causes of maternal deaths are mostly considered preventable. Since the strategies contemplate the identification of priority interventions to be applied, use of protocols, good infrastructure, equipment, medications, adequate number of personnel and good management of services, method of menstrual regulation as prevention of illegal abortion. In this way, the strategies are reported by simple measures, often of low cost and that do not require high technology apparatus. The totality of studies that address strategies to reduce maternal mortality are of an international nature.